Antioxidant peptides released from soybean by lactic acid bacteria with proteolytic activity - Quiroga, Maria (2021)
Biopeptides are fragments encrypted in a precursor protein. They possess a particular amino acid sequence and specific biofunctional attributes that can influence the main systems of an organism when released by proteolysis. Glycinin and βconglycinin are the main proteins in soybean (which in turn is the main protein source in poultry feeds), and many amino acidic sequences with different features, such as antioxidant properties, are included in them. On the other hand, microorganisms are an important source of proteolytic enzymes. They could act on soybean proteins and release biofunctional peptides that may possess antioxidant properties. Therefore, the aim of this work was the study of the antioxidant activity of the biopeptides released from soybean protein isolate (SPI, which contains only glycinin and β-conglycinin) by three lactic acid bacteria (Enterococcus italicus LET 302, E. faecium LET 303 and Lactobacillus brevis LET 216) previously isolated from soybean flour. To this end, each strain was incubated for 16 h in broth with SPI as the sole protein source. Then, the supernatants were recovered by centrifugation and sterilized by filtration with 0.22 µm pore membranes. In order to obtain different peptidic fractions, the supernatants were centrifuged with 10 kDa filters, and the filtrates were centrifuged again with 3 kDa filters. This way, three fractions were obtained for each strain: M1 (peptides > 10 kDa), M2 (3 kDa < peptides < 10 kDa), and M3 (peptides < 3 kDa). Protein concentration was assessed by Bradford, and the amount of protein on each fraction was adjusted to 0.3 µg before the antioxidant activity was determined by DPPH assay. Antioxidant activity was observed on the three fractions from all strains, and M3 presented the highest activity in all cases. Comparing the respective fractions from different strains, higher antioxidant activity was always showed by E. faecium LET 303, followed by E. italicus LET 302 and L. brevis LET 216. In conclusion, the proteolytic enzymes expressed by the strains of lactic acid bacteria studied could act on soybean proteins, releasing peptides with antioxidant activity. The hydrolysis of these proteins, in a treatment before their consumption by poultry or in situ by these bacteria administered as feed additive, could improve their digestion as well as collaborate with the oxidative metabolism of cells in the digestive system.